2021
DOI: 10.1111/cobi.13698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stewardship on protected area effectiveness for coastal birds

Abstract: Evaluation of protected area effectiveness is critical for conservation of biodiversity. Protected areas that prioritize biodiversity conservation are, optimally, located and managed in ways that support relatively large and stable or increasing wildlife populations. Yet evaluating conservation efficacy remains a challenging endeavor. We used an extensive community science data set, eBird, to evaluate the efficacy of protected areas for birds across the Gulf of Mexico and Atlantic coasts of the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This is an important framing, as even with expansion of protected areas, biodiversity loss and extinction rates continue to remain high (Crist et al, 2021). Therefore, protection status alone does not guarantee conservation success without additional management actions (Michel et al, 2021; Wauchope et al, 2022; Wood et al, 2014). This may be the case within the context of climate change, where proactive management strategies need to be implemented to continuously adapt to changing environmental conditions (Schuurman et al, 2020; Wu et al, 2018, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important framing, as even with expansion of protected areas, biodiversity loss and extinction rates continue to remain high (Crist et al, 2021). Therefore, protection status alone does not guarantee conservation success without additional management actions (Michel et al, 2021; Wauchope et al, 2022; Wood et al, 2014). This may be the case within the context of climate change, where proactive management strategies need to be implemented to continuously adapt to changing environmental conditions (Schuurman et al, 2020; Wu et al, 2018, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Shorebird conservation-specific research has found that non-compliance may vary by type of dog regulation (e.g. complete dog closures compared to leashing areas; Maguire et al, 2019) and that sites with steward programs have positive impacts on shorebirds, especially in the summer (Michel et al, 2021). Still, there is a need for an evaluation of the efficacy (in terms of increased compliance with dog regulations) for enforcement vs. voluntary compliance vs. combined approaches to validate if the combined approach suggested in the conservation criminology literature and our interview findings is indeed most effective.…”
Section: Future Directionsmentioning
confidence: 99%
“…The National Audubon Society's conservation efforts include both broad-scale national and international, as well as local, site-based conservation programs. To ensure that its conservation programs are informed by science, Audubon has invested in spatial analyses across multiple scales (e.g., Audubon Alaska 2019, Grand et al 2019Saunders et al 2019;Bateman et al 2020b;Michel et al 2020;DeLuca et al 2021;Michel et al 2021). The utility of these investments is measured by the degree to which they can support state and regional efforts throughout the hemisphere to advance on-theground conservation and policy.…”
Section: Introductionmentioning
confidence: 99%